Tatyana Bagishevna Nikitina’s Anniversary - Alexander V. Akilbaev (Археология евразийских степей)
The paper describes the main fields of the research work by Doctor of History, chief research fellow at the Mari Research Institute of Language, Literature and History named after V.M. Vasiliev, famous specialist in medieval archaeology Tatyana Bagishevna Nikitina, who celebrated her anniversary on July 27, 2024. T.B. Nikitina began to study archaeology while still at the Mari State University. After graduation she came to work at the Mari Research Institute, where she still works. The scientific interests of the jubilarian are related with the medieval archaeology of the Mari people, the areas where they live. Initially it was burial grounds of XVI–XVIII centuries, then the sphere of study expanded to the whole medieval era. For the period of scientific activity of the researcher till today more than 200 scientific articles and 9 monographs have been published.